Transgenic Suppression of AGAMOUS Genes in Apple Reduces Fertility and Increases Floral Attractiveness - Klocko, Amy L. (PLoS One, 2016)
We investigated the ability of RNA interference (RNAi) directed against two co-orthologs of AGAMOUS (AG) from Malus domestica (domestic apple, MdAG) to reduce the risks of invasiveness and provide genetic containment of transgenes, while also promoting the attractiveness of flowers for ornamental usage. Suppression of two MdAG-like genes, MdMADS15 and MdMADS22, led to the production of trees with highly showy, polypetalous flowers. These “double-flowers” had strongly reduced expression of both MdAG-like genes. Members of the two other clades within in the MdAG subfamily showed mild to moderate differences in gene expression, or were unchanged, with the level of suppression approximately proportional to the level of sequence identity between the gene analyzed and the RNAi fragment. The double-flowers also exhibited reduced male and female fertility, had few viable pollen grains, a decreased number of stigmas, and produced few viable seeds after cross-pollination. Despite these floral alterations, RNAi-AG trees with double-flowers set full-sized fruit. Suppression or mutation of apple AG-like genes appears to be a promising method for combining genetic containment with improved floral attractiveness.